On Rough ℐ2-Convergence of Double Sequences. (2nd April 2016) - Dündar, Erdínç
ABSTRACT: In this study, we introduce the notion of rough ℐ2 -convergence and the set of rough ℐ2 -limit points of a double sequence and obtained two rough ℐ2 -convergence criteria associated with this set. Later, we proved that this set is closed and convex. Finally, we examined the relationships between the set of cluster points and the set of rough ℐ2 -limit points of a double sequence.